ANALISIS PENGARUH JUMLAH PENDUDUK, PRODUK DOMESTIK REGIONAL BRUTO (PDRB), INFLASI DAN JUMLAH TENAGA KERJA TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA MALANG TAHUN 2012-2021 - Surya Andriansyah, Afwanda; Moh. Athoillah (Journal of Development Economic and Social Studies, 2024)
This study aims to determine the effect of total   population,   Gross   Regional Domestic Product (GDP), inflation and total employment to Region Own-Source Revenue (PAD) in 2012-2021. This study used qualitative approach and literature review method. The data were obtained from Central Bureau of Statistics and the annual financial reports of Malang City through the official website which can be accessed by the public. The results of this study indicated that the variables of total population, inflation and total employment do not have a significant influence on Region Own-Source Revenue (PAD). However, Gross Regional Domestic Product (GDP) has a positive and significant influence on Region Own-Source Revenue (PAD). Meanwhile, total population, Gross Regional Domestic Product (GDP), inflation and total employment have a simultaneous influence of 96,4% on Region Own-Source Revenue (PAD).